Exterior Noise Due to Interaction of Tire-Thermoplastic Transverse Rumble Strips - HARON, Zaiton; OTHMAN, Mohd Hanifi; HEE, Lim Meng; YAHYA, Khairulzan; HAININ, Mohd Rosli; DARUS, Nadirah; LEONG, Mohd Salman (Archives of Acoustics, 2017)
Transverse rumble strips (TRS) are a common choice to reduce vehicle speed and increase driver alertness on roadways. However, there is a potential trade-off using them on rural roadway due to the noise problem created when vehicles go over the strips. The present study investigated the noise level, spectral analysis, and the possible noise generation mechanism when the TRS is hit by a vehicle. Tenraised-rumbler (RR) and three-layer-overlapped (TLO) TRS were selected in this study as they have received complaints from the public. Results showed that RR generated a relatively higher noise and impulse at a low speed, and increased sound level in each octave band. Based on these results, RR may irritate human ears even when the vehicle travels at a low speed. It was found that RR increased all noise generation mechanisms of tyre-pavement interaction whilst TLO increased structural resonance, sidewall and surface texture vibration.